Balance Scorecard (BSC) PT. Pos Indonesia (PERSERO) - Adibakhara, Muhammad Gusti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Balanced scorecard (BSC) is one of the performance measurement alternatives that aims to combine financial and non-financial performance measures. This measurement is the result of a process based on the mission and strategy of a company. There are four specs measured in the balanced scorecard (BSC), namely the financial perspective, the consumer customer perspective, the perspective of the business process and the perspective of growth and learning. The performance improvement is viewed from four perspectives, namely the financial perspective, the customer perspective, the perspective of internal business processes, and the perspective of learning and growth. Through the mechanism of cause and effect, the financial perspective becomes the main benchmark explained by the other three benchmarks, namely from three perspectives.